ATP Induces Mild Hypothermia in Rats but has a Strikingly Detrimental Impact on Focal Cerebral Ischemia. Issue 1 (January 2013) - Zhang, Meijuan; Li, Wenjin; Niu, Guangming; Leak, Rehana K; Chen, Jun; Zhang, Feng
Ischemic stroke is a devastating condition lacking effective therapies. A promising approach to attenuate ischemic injury is mild hypothermia. Recent studies show that adenosine nucleotides can induce hypothermia in mice. The purpose of the present study was to test the hypothesis that adenosine 5′-triphosphate (ATP) induces mild hypothermia in rats and reduces ischemic brain injury. We found that intraperitoneal injections of ATP decreased core body temperature in a dose-dependent manner; the dose appropriate for mild hypothermia was 2 g/kg. When ATP-induced hypothermia was applied to stroke induced by middle cerebral artery occlusion, however, a neuroprotective effect was not observed. Instead, the infarct volume grew even larger in ATP-treated rats. This was accompanied by an increased rate of seizure events, hemorrhagic transformation, and higher mortality. Continuous monitoring of physiologic parameters revealed that ATP reduced heartbeat rate and blood pressure. ATP also increased blood glucose, accompanied by severe acidosis and hypocalcemia. Western blotting showed that ATP decreased levels of both phospho-Akt and total-Akt in the cortex. Our results reveal that, despite inducing hypothermia, ATP is not appropriate for protecting the brain against stroke. Instead, we show for the first time that ATP treatment is associated with exaggerated ischemic outcomes and dangerous systemic side effects.